ANALISIS PENGARUH BOOK-TAX DIFFERENCES TERHADAP PERSISTENSI LABA PADA PERUSAHAAN PROPERTI DAN REAL ESTAT YANG TERDAFTAR - Puspa Negara B51110070, Lusiana Joef (Jurnal KIAFE, 2014)
This study aims to obtain empirical evidence about the influence of book tax differences on the persistence of earnings before taxes. Independent variables used book tax differences which are composed of permanent differences and temporary differences. Then the dependent variable used is the persistence of profit before tax which is a proxy of the change in income before taxes between accounting profit before tax of the future period with a profit before tax of the current period. The population in this study is the property and real estate company listed on the Indonesia Stock Exchange in 2010-2012. Data were obtained from the financial statements of the company property and real estate the period 2010-2013. Based on purposive sampling method, samples obtained by 12 companies. This hypothesis was tested using multiple regression analysis. The results showed that permanent differences significantly influence the persistence of earnings before taxes. While the temporary differences do not significantly affect persistence of earnings before taxes. Keywords: book-tax differences, permanent differences, temporary differences, earnings persistence